Language Employment in Children of Two Years Old in Mataram, West Nusa Tenggara Barat - Hastuti, Hilda; Suktiningsih, Wiya (JOLLT Journal of Languages and Language Teaching, 2019)
This research aims to describe language acquisition in children age 2 years especially in the realm of syntax at PAUD Santa Maria Mataram City. This research is synchronic research used the qualitative method which was descriptive method. The subject of this research was the children age 2 years at PAUD Santa Maria and the object of this research was language acquisition which was the acquisition of declarative, interrogative, and imperative.Â The data was collected by simak libat baca technique and simak libat catat.Â After the data was analyzed, the data was classified into the acquisition of declarative, interrogative, and imperative. Based on the data analysis that has done, found language acquisition of children age two years from April to May were 54 declaratives, 18 imperatives, and 13 interrogatives. The result of this study also shows that the children age 2 years are more likely used declarative sentences than interrogative and imperative in the daily conversation.